Efforts to Improve Students' Analytical Skills in Islamic Religious Education Learning by Using the Discovery Learning Model - Muslim, Buhori (MANDAILING GLOBAL EDUKASIA, 2024)
The purpose of this study is to improve students' analytical skills in Islamic Religious Education subjects. This classroom action research was carried out with a time allocation of 3 teaching hours, 2 meetings and implemented in 2 cycles. If the first cycle has not shown the expected results, it will be continued in the next cycle (cycle II). iii Actions in cycle II are improvements and refinements of the actions carried out in cycle I. Therefore, the actions in cycle II were carried out by looking at the results of observations of teaching and learning activities and student learning outcomes in cycle I. The material taught in accordance with the Mapping of Competency Standards, Basic Competencies and Indicators in class XI is material about faith in the books of Allah. The learning outcomes obtained by students through written tests at the end of the lesson for cycle I were 10 students (50%) who had achieved learning completion and there were still 10 students (50%) who had not achieved learning completion with student absorption reaching 77.69%. In cycle II there was an increase to 20 people (100%) who achieved learning completion with student absorption reaching 83.9%. Observations on teaching and learning activities in cycle I 5 aspects (62.5%) obtained good criteria and 3 aspects (37.5%) obtained sufficient criteria. In the second cycle increased to 7 aspects (87.5%) obtained good criteria and only 1 aspect (12.5%) obtained sufficient criteria Based on the results of the research and discussion conducted, it is clear that through the Discovery Learning Learning Model and its use in Islamic Religious Education subjects for the material of faith in the books of Allah, students experienced an increase in learning outcomes. Likewise, in the implementation of learning there was an increase in Suggestions, the use of appropriate and interesting media, time allocation and student organization need to be considered in order to achieve efficiency and effectiveness of student learning outcomes.